STUDI HUBUNGAN KESIAPAN BELAJAR DENGAN PRESTASI BELAJAR MATEMATIKA PADA ANAK TUNAGRAHITA RINGAN - NUR ROHMATIN, ETIKA (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Learning readiness was a condition which needed to be prepared before doing or beginning some learning activities. To mentally retardation, learning readiness was absolute to be needed in reaching their studying achievement. The learning readiness included physic readiness, mental readiness, and material readiness.This research had purpose to know whether there was relationship between learning readiness and learning achievement of mathematics to mentally retardation or not. The subject of this research was mild mentally retardation. This research used quantitative kind with correlation arrangement to know whether there was significant relationship between learning readiness and learning achievement of mathematics readiness to mild mentally retardation or not. The data was collected using questionnaire technique, observation, and documentation. The technique of data analysis used was statistic non parametric, with n = 10 and α = 5% and then it was processed using spearman rank correlation with the aim of SPSS (Statistical Program for Social Science) software V.23 for windows. The result of data analysis in this research was obtained that p = 0,871 was greater than p table in the significant level either 5% = 0,648 or 1% = 0,794 so the interpretation was p counted > p table which meant Ho was accepted and Ha was rejected. The data analysis of this research indicated that the correlation between variable X (learning readiness) and Variable Y (learning achievement) were in high category and there was real / significant relationship between learning readiness and learning achievement of mathematics to mild mentally retardation.   Keywords: Learning readiness, learning achievement of mentally retardation